Analysis of compliance with the entity principle in two service providers (Research, Society and Development, 2020)
Objective: The present work aimed to investigate the compliance with the principle of the entity in two service companies of Zona da Mata Mineira and to verify the behavior adopted from the knowledge about it, its application, and the benefits or difficulties found in its use or not. Method: This is a qualitative research, seeking, through content analysis, to interpret the view of company managers regarding the principle of accounting entity. Results: From the research results, it was possible to identify that both managers do not have a definition of the principle. Moreover, it was found that, in one of the institutions, the said principle is applied, with the manager having a minimum accounting knowledge. In turn, in the other institution, it was found a complete non-compliance with it, and a partial knowledge about standards. Accounting. Theoretical Contributions: Through the research, it was possible to make a parallel between the companies regarding such practices and observe, in the face of the differences found, the benefits of the studied principle. Social / managerial contributions: It is hoped that the research can contribute significantly to the organizations and managers who will be aware of this article, so that they can better understand the principle, its characteristics and its importance.